Patient Controlled Analgesia Used to Assess the Efficacy and Potency of a New Opioid - Brian Ginsberg; Katherine P Grichnik; Margaret Muir; Michael Damask; Peter S Glass (Pain Research and Management)
Patient controlled analgesia (PCA) is widely used for the management of postoperative pain. PCA also permits a comparison to be made among analgesics in the clinical setting because it limits the variability introduced by third parties. Use of PCA to establish efficacy and potency data for an investigational drug, pentamorphone, compared with morphine is reported. Pentamorphone was found to be more efficacious than morphine in the first hour after surgery because significantly more patients were able to achieve a visual analogue scale of less than 30 mm with pentamorphone. Thereafter pentamorphone and morphine were found to be equally efficacious. Initially pentamorphone may be more potent than morphine based on the greater volume of morphine used in the first hour of therapy. However, a potency ratio could not be determined because this result was under conditions of unequal analgesia. The potency ratio determined at 24 h of therapy under equianalgesic conditions (252:1) is similar to previously reported potency data from laboratory studies (200:1). This study supports the use of PCA as a model to investigate and compare new drugs to establish their efficacy and potency.